Analysis of the Influence of Brand Equity on Consumer Purchase Decisions in the Modern Retail Market - Erislan Erislan (Mandalika Institute, 2025)
This study aims to analyze the influence of brand equity on consumer purchasing decisions in the modern retail market. Brand equity, which includes brand awareness, brand association, quality perception, and brand loyalty, is a strategic element in building long-term relationships with consumers and creating a competitive advantage. This study uses a literature study approach by examining theories and related empirical findings. The results of the analysis show that each component of brand equity has a significant influence on consumers' purchasing decisions, with the perception of quality and brand loyalty as the dominant factors. Brand awareness and brand associations also make an important contribution in shaping consumer preferences. These findings underscore the importance of effective brand equity management through integrated marketing strategies to increase brand appeal and customer loyalty in the modern retail market. This research is expected to be a reference for business practitioners in developing brand equity-based marketing strategies.